Muslim-friendly hospital services framework - Jamaludin, Mohammad Aizat; Kartika, Betania; Ramli, Mohd Anuar; Hamzah, Muhammad Hazrul (Jabatan Kemajuan Islam Malaysia, 2019)
The Shariah-Compliant healthcare system is an urgent demand for Muslim consumers. It guarantees the pipeline of Shariah-Compliant and Halalan Tayyiban chain from farm to hospital bedside. Therefore, this study focuses on the concept and framework of Muslim-friendly hospital services in Malaysia pertaining to Shariah Compliance. This study conducts qualitative approaches based on the library research and expert interviews. The collected data is analysed further, and the results show that the concept of Muslim Friendly Hospital services is in accordance with Shariah principles which include the aspects of physical, emotional and spiritual demands of Muslim patients. In brief, this paper highlights that the implementation of Muslim Friendly Hospital should initial from the preparation of medicines up to the provision of medical treatment and sufficient facilities. Hence, Muslim-Friendly Hospital services benefit both Muslim and non-Muslim patients alike.